FMRP Regulates Neurogenesis In Vivo in Xenopus laevis Tadpoles(1,2,3) - Faulkner, Regina L. (eNeuro, 2014)
Fragile X Syndrome (FXS) is the leading known monogenic form of autism and the most common form of inherited intellectual disability. FXS results from silencing the FMR1 gene during embryonic development, leading to loss of Fragile X Mental Retardation Protein (FMRP), an RNA-binding protein that regulates mRNA transport, stability, and translation. FXS is commonly thought of as a disease of synaptic dysfunction; however, FMRP expression is lost early in embryonic development, well before most synaptogenesis occurs. Recent studies suggest that loss of FMRP results in aberrant neurogenesis, but neurogenic defects have been variable. We investigated whether FMRP affects neurogenesis in Xenopus laevis tadpoles that express a homolog of FMR1. We used in vivo time-lapse imaging of neural progenitor cells and their neuronal progeny to evaluate the effect of acute loss or overexpression of FMRP on neurogenesis in the developing optic tectum. We complimented the time-lapse studies with SYTOX labeling to quantify apoptosis and CldU labeling to measure cell proliferation. Animals with increased or decreased levels of FMRP have significantly decreased neuronal proliferation and survival. They also have increased neuronal differentiation, but deficient dendritic arbor elaboration. The presence and severity of these defects was highly sensitive to FMRP levels. These data demonstrate that FMRP plays an important role in neurogenesis and suggest that endogenous FMRP levels are carefully regulated. These studies show promise in using Xenopus as an experimental system to study fundamental deficits in brain development with loss of FMRP and give new insight into the pathophysiology of FXS.